2020
DOI: 10.3390/polym12092169
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitosan—Graphene Oxide Composite Aerogel by Hydrothermal Method and Its Adsorption Property of Methyl Orange

Abstract: Graphene based aerogel has become one of the most likely functional adsorption materials that is applicable to purify various contaminated water sources, such as dye wastewater, because of its high porosity, structural stability, large specific surface area, and high adsorption capacity. In this study, chitosan and graphene oxide were first selected as the matrix to prepare the composite hydrogel through the hydrothermal method, which was further frozen and dried to obtain the target aerogel. The microscopic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The adsorption equilibrium is obtained when using a constant temperature; there is a remarkable distribution of SMZ in the solution and onto the adsorbent surface in a way, there is complete adsorption. We studied the isotherms to help understand the behavior and capacity of adsorption systems (Zhu et al, 2020).…”
Section: Adsorption Equilibrium Isothermmentioning
confidence: 99%
“…The adsorption equilibrium is obtained when using a constant temperature; there is a remarkable distribution of SMZ in the solution and onto the adsorbent surface in a way, there is complete adsorption. We studied the isotherms to help understand the behavior and capacity of adsorption systems (Zhu et al, 2020).…”
Section: Adsorption Equilibrium Isothermmentioning
confidence: 99%
“…Chemicals such as aldehydes, genipin, formaldehyde, glyoxal, and glutaraldehyde have been used in the chemical crosslinking of chitosan [ 64 ]. It should be noted, however, that a recent study comparing the sol–gel/crosslinking method with the alternative hydrothermal method showed that the latter could be used to produce a chitosan-graphene aerogel with a higher methyl-orange absorption rate of 96.6% [ 23 ]. In addition, a low temperature of 140 °C during hydrothermal treatment has been shown to result in a higher removal efficiency of metal ions compared to that obtained at the higher temperatures of 180 and 215 °C due to an increase in the crystallinity of the sample obtained at low temperature [ 20 ].…”
Section: Preparation Of Porous Polysaccharidesmentioning
confidence: 99%
“…The density of an aerogel can be as low as 0.004–0.5 g/cm 3 with a high porosity of up to 99.8% and a large specific surface area of 100–1600 m 2 /g [ 11 ]. Due to these properties, the aerogels have been applied as adsorbents of CO 2 [ 12 , 13 , 14 , 15 , 16 ], dyes, and heavy metals [ 2 , 3 , 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], as tissue engineering and blood system scaffolds in the biomedical field [ 3 , 22 , 23 , 24 , 25 , 26 , 27 ], and as materials for thermal insulation [ 4 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and food packaging [ 37 , 38 , 39 , 40 , 41 ]. These versatile materials also exhibit high optical transparencies, low thermal conductivities (down to 12 mW/mK) and low sound speeds [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the intense collision between colloidal particles promotes the secondary pore formation of composite oxides under hydrothermal conditions, whereas the condensation between colloidal particles is a very slow process at room temperature. Therefore, the hydrothermal process is conducive to the formation of a more developed pore network structure, thereby improving the specific surface area and pore volume of Mg1Zr2-HT [31]. In addition, the dissolution deposition/crystallization process also occurs in the hydrothermal process [32].…”
Section: Effect Of Preparation Methodsmentioning
confidence: 99%